Electronic scoreboard part 1 / Wan Marhana Lailie Wan Mahmud and Mohd Uzir Kamaluddin - Wan Mahmud, Wan Marhana Lailie; Kamaluddin, Mohd Uzir (1985)
There are many types of display devices available nowadays. These display devices are being used to display information. The display may be static or dynamic. That is, the display can either be stationary display or a moving display. The one that emphasize is placed more is on the stationary display. The project, an electronic scoreboard is an example of stationary display. The electronic scoreboard, can display any information on its display panel. This information can be changed easily to suit the purpose it is being used for. Score boards are normally used in stadiums to keep spectators informed of events and results occurring. It can also be used in seminars, stage shows, convocation etc. to keep the audience informed of what is happening.